Compounds targeting ferroptosis in breast cancer: progress and their therapeutic potential - Chuchu Xu; Chuchu Xu; Yian Chen; Yian Chen; Qinghong Yu; Qinghong Yu; Jiaqing Song; Jiaqing Song; Ying Jin; Ying Jin; Xiufei Gao; Xiufei Gao (Frontiers in Pharmacology, 2023)
In recent years, there has been a significant increase in the incidence of Breast cancer (BC), making it the most common cancer among women and a major threat to women’s health. Consequently, there is an urgent need to discover new and effective strategies for treating BC. Ferroptosis, a novel form of cell death characterized by the accumulation of iron-dependent lipid reactive oxygen species, has emerged as a distinct regulatory pathway separate from necrosis, apoptosis, and autophagy. It is widely recognized as a crucial factor in the development and progression of cancer, offering a promising avenue for BC treatment. While significant progress has been made in understanding the mechanisms of ferroptosis in BC, drug development is still in its early stages. Numerous compounds, including phytochemicals derived from dietary sources and medicinal plants, as well as synthetic drugs (both clinically approved medications and laboratory reagents), have shown the ability to induce ferroptosis in BC cells, effectively inhibiting tumor growth. This comprehensive review aims to examine in detail the compounds that target ferroptosis in BC and elucidate their potential mechanisms of action. Additionally, the challenges associated with the clinical application of ferroptosis-inducing drugs are discussed, offering valuable insights for the development of novel treatment strategies for BC.